Nitraria sibirica Pall.: A Halophytic Resource for Antioxidant-Rich Functional Foods and Ecological Resilience - Keyi Lu; Xinmei Zhang; Liping Zhao; Jikun Xu; Jianmei Li (Foods)
Nitraria sibirica Pall., a halophytic shrub native to arid and saline–alkaline ecosystems, represents a dual-purpose resource for ecological stabilization and functional food development. This review synthesizes current knowledge of its bioactive compounds and pharmacological properties, while identifying research gaps in stress-induced metabolic regulation. The plant contains diverse phytochemicals including phenolic glycosides (e.g., clovin), alkaloids (e.g., nitraramine), immunomodulatory polysaccharides, and anthocyanins, which collectively demonstrate superior antioxidant capacity (freeze-dried polysaccharides outperform Butylated Hydroxytoluene (BHT)), significant antihypertensive effects via angiotensin-converting enzyme (ACE) inhibition and nitric oxide (NO) pathway activation, and broad-spectrum antimicrobial activity against foodborne pathogens. Notably, its pectin components reduce allergen absorption by 72%, suggesting potential as hypoallergenic food additives. These findings validate traditional medicinal uses while revealing novel applications in functional foods and nutraceuticals. Despite promising preclinical results, key challenges remain in understanding compound synergies under environmental stress and translating findings to human applications. Future research should employ multi-omics approaches to elucidate stress-adaptive phytochemical biosynthesis, coupled with clinical validation and sustainable cultivation methods. As a model species for ecological and nutritional applications, N. sibirica offers innovative solutions for addressing both global health challenges (metabolic disorders) and environmental concerns (soil rehabilitation), positioning it at the forefront of climate-resilient agricultural innovation.